“Folk” Art on a Prescribed Pattern: Soviet Propaganda in Lacquer Crafts of the 1920–1950s, Based on Drawings by Urban Professional Artists - Lavrov, Dmitrii E. (Actual Problems of Theory and History of Art, 2018)
The article concerns the paths of administrative and artistic leadership in Russian lacquer crafts, expressed in imposing ready professional drawings upon lacquer crafts products of Soviet Russia in the 1920–1950s. The paper examines different arguments of Soviet art critics for such interference in the internal processes of Russian folk art; the reasons for the rejection of Russian peasant artists; preserved examples of Soviet lacquers with “ready-made” agitation images. Despite the extreme persistence of the attempts to penetrate “ready” professional drawings (which had been created by professional urban artists from Moscow for the Russian provincial artisans) in the lacquer goods, this artistic and ideological practice was not accepted in any major lacquer craft center of Soviet Russia (Palekh, Mstiora, Kholui, and Fedoskino). However, undoubtedly this practice had a significant impact on their further development (in particular, on painting of premium tin cups by Fedoskino lacquer miniaturists in the 1940–1950s). In the conclusion of the report, the legitimacy of the creative work is demonstrated even in such ideologically-based field of Soviet folk crafts as lacquer articles with Communist political propaganda.